KEDISIPLINAN DAN KINERJA KARYAWAN PT LAJU PERDANA INDAH, SITE KOMERING SUMATERA SELATAN - Rizaldi, M Yanuar; Sayekti, Wuryaningsih Dwi; Indriani, Yaktiworo (Lampung University, 2015)
This research aims to know the discipline level and performance of employees, the influence of individual characteristics on performance of employee through direct or indirect discipline, and the influence of discipline on performance of employee. This research was conducted at PT Laju Perdana Indah site Komering South Sumatera, in Plantation Department specifically in Division 1st and 4th. Data of this research was taken from January until February 2015 by a sensus methode that using 81 employees. Research data was analyzed by descriptive and verificative analysis. The results showed that the discipline level of employees in Division 1st and 4thof PT Laju Perdana Indah was good enough and in average the employees performance had already met the expectations. The period of work and ethnic had significantly direct influence on performance of employees, while employee’s age, education, and ethnic did not have influence on performance of employees. The employee discipline was significantly influence on performance of employees. Key words: employee discipline, employee performance, individual characteristics